Residual Selenium Distribution and Risk in Shatt Al-Basrah Sediments: Distribusi Selenium Sisa dan Risiko dalam Sedimen Shatt Al-Basrah - Zuhair A. Abdulnabi; Maha K. AL-Mishrey; Kareim A. Abdulkareim; Tokha, K. Shaker; Hamid T. AL-Saad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Selenium is a trace element with complex geochemical behavior that can pose ecological and human health concerns when accumulated in aquatic environments. Specific Background The Shatt Al-Basrah Channel in southern Iraq is exposed to increasing industrial, agricultural, and urban pressures, yet detailed assessments of selenium behavior in sediment cores remain limited. Knowledge Gap Vertical distribution patterns and contamination severity of residual selenium in this channel have not been comprehensively evaluated using combined geochemical indices and health risk indicators. Aims This study aimed to quantify residual selenium concentrations, assess vertical and spatial distribution, identify natural and anthropogenic sources, and evaluate ecological and human health risks. Results Selenium concentrations ranged from 3.69 to 18.50 ppb, with highest values in surface sediments, particularly at Stations 2 and 3. Enrichment factor, contamination factor, and geoaccumulation index values indicated moderate contamination primarily linked to anthropogenic inputs. Novelty The study integrates residual fraction analysis with contamination indices and risk assessment across sediment depths in the Shatt Al-Basrah Channel. Implications The findings provide a baseline for future monitoring and support management strategies to reduce selenium inputs and potential long-term ecological and health risks in the northwest Arabian Gulf. Keywords: Selenium Contamination, Sediment Cores, Shatt Al-Basrah Channel, Ecological Risk, Anthropogenic Sources Key Findings Highlights: Surface sediments exhibited consistently higher selenium concentrations than deeper layers. Contamination indices indicated moderate enrichment associated with human activities. Residual selenium levels suggest potential long-term ecological and dietary exposure concerns.